Regional integration and business localizations: A long run approach to the cork industry in the Iberian Peninsula - Amélia Branco; Jo\~ao Lopes; Francisco Parejo; José Preciado (European Regional Science Association (ERSA), 2013)
The cork sector is a relevant case study given the economic importance of this industry for some regions (value added, employment and rural development). This industry is also important because of its contribution to environmental sustainability as it uses a natural renewable raw material. Portugal and Spain are the most important producers of cork and exporters of manufactured cork products (stoppers and agglomerates). The main purpose of this paper is to study the economic integration and the historical changes of cork business localization in the Iberian Peninsula. We start by studying the historical roots, motivations and economic consequences of the delocalization of Catalonian firms to Portugal during the first quarter of the 20th century. Then a comparison is made with the recent process of delocalization of an anchor firm of Aveiro industrial district (Corticeira Amorim) to Spain. The theoretical framework of this study is the industry and cluster life cycles as well as the recent insights from the evolutionary economic geography.
Keywords: R11; R12; L73; 330; cork industry; business location; clusters; Iberian Peninsula